Material for high-performance injection mold and preparation method thereof

By adding specific elements and multi-step heat treatment process to the injection mold material, excellent tempered cortexite structure is formed, which solves the internal quality defects and dimensional deviation of the injection mold, and improves the wear resistance and service life of the mold.

CN119265478APending Publication Date: 2025-01-07NANCHANGXING ELECTRONIC CONTROL SYST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411181227.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

There are problems such as internal quality defects and coarse tissue grains during the forming process of existing injection molds, resulting in poor wear resistance and short life of the mold, and dimensional deviations after the use of precision plastic products.

Method used

High-performance injection mold materials composed of specific mass percentages, including C, Si, Mn, Cr, Mo, Ni, V and other elements, are used to pass vacuum induction sintering and multi-step heat treatment processes, including vacuum water quenching, refrigeration and laser quenching heat treatment. , forms excellent tempered cortexite structure, improves the comprehensive mechanical properties and corrosion resistance of the mold.

Benefits of technology

It significantly improves the wear resistance, thermal strength and plastic toughness of the mold, extends the service life, and stabilizes the size, solves the problem of dimensional deviation, and improves the overall performance of the mold.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a material for a high-performance injection mold and a preparation method of the material. The material comprises the following components in percentage by mass: 0.30-0.40% of C; 0.20% to 0.40% of Si; mn: 1.2 to 1.5%; 1.5 to 2.0 percent of Cr; 1.5 to 2.0 percent of Mo; 0.8% to 1.2% of Ni; 0.2 to 0.4 percent of V and the balance of Fe. According to the material for the injection mold, alloy elements such as Ni, Mo and V are added on the basis of medium carbon steel during burdening, crystal grains are refined, the hardenability is improved, and meanwhile the strength, wear resistance and plasticity and toughness of the material are improved. Ni and Cr alloy elements are also beneficial to improving the corrosion resistance of the injection mold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mold material preparation, and in particular to a high-performance injection mold material and a preparation method thereof. Background Art

[0002] With the continuous development of industrial technology, the application of plastic products is becoming more and more extensive, especially in the automotive, electronic, electrical and instrumentation industries. Therefore, in recent years, the demand for molds for plastic product forming has increased rapidly. The output value of molds for plastic products in many developed countries or regions has even exceeded that of cold-working molds, and it ranks first in the mold manufacturing industry. Most plastic products are formed by compression molding. Regardless of the molding of thermoplastics or thermosetting plastics, the working temperature of the pressed plastic is usually 200-250℃. According to the working conditions of the plastic mold, higher requirements are put forward for the steel used for the mold. The mold should have high hardness and wear resistance, and be able to maintain a certain surface roughness for a long time; have sufficient strength and toughness, and be able to withstand a certain load without deformation; have certain corrosion resistance, especially for chlorine-containing plastic products. In addition, the mold is required to have small deformation after heat treatment to ensure the matching accuracy, especially for precision plastic products.

[0003] Conventional injection molds have problems such as internal quality defects and coarse grains in the molding process, which lead to poor mold wear resistance, short life, and easy mold cracking. In addition, for precision plastic products, conventional injection molds have dimensional deviation problems after being used for a period of time. Therefore, it is necessary to upgrade traditional plastic mold materials and preparation methods to improve their comprehensive performance and extend the service life of the mold. Summary of the invention

[0004] Purpose of the invention: In order to solve the problems of internal quality defects and coarse grain size in the injection mold forming process in the prior art, and to solve the problem of dimensional deviation of precision injection molds after use, the present invention specifically provides a high-performance injection mold material and a preparation method thereof.

[0005] Technical solution: The high-performance injection mold material of the present invention comprises the following components in percentage by mass: C: 0.30~0.40%; Si: 0.20~0.40%; Mn: 1.2~1.5%; Cr: 1.5~2.0%; Mo: 1.5~2.0%; Ni: 0.8~1.2%; V: 0.2~0.4%, the balance is Fe.

[0006] In some embodiments, the Si is added in the form of ferrosilicon containing 73% Si, the Mn is added in the form of ferromanganese containing 65% Mn, the Cr is added in the form of low-carbon ferrochrome containing 57% Cr, the Mo is added in the form of molybdenum plate containing 55% Mo, the Ni is added in the form of pure nickel plate, and the V is added in the form of ferrovanadium containing 50% V.

[0007] Furthermore, 0.30~0.40%C makes the material have better comprehensive mechanical properties (strength and toughness) after heat treatment.

[0008] Furthermore, 0.20-0.40% Si has a solid solution strengthening effect and improves hardenability.

[0009] Furthermore, 1.2~1.5% Mn can prevent hot brittleness and strongly improve the hardenability of steel to improve wear resistance.

[0010] Furthermore, 1.5~2.0% Cr can increase the high temperature oxidation resistance and corrosion resistance of steel in oxidizing media.

[0011] Furthermore, 1.5-2.0% Mo improves hardenability, reduces or inhibits the temper brittleness of other alloy elements, and improves hot strength.

[0012] Furthermore, 0.8~1.2% Ni has the effect of refining grains, increasing the plasticity and toughness of steel, and improving the corrosion resistance of steel.

[0013] Furthermore, 0.2~0.4%V can improve the tempering resistance of steel, has a strong secondary hardening effect, and has the effect of grain hardening.

[0014] On the other hand, the present invention also discloses a method for preparing a high-performance injection mold material, comprising the following steps: S1. According to the mass ratio of each element, select suitable raw materials for calculation and batching; S2. Put the prepared raw materials into the crucible of the vacuum induction melting furnace, cover the furnace cover, close the vent valve, start the vacuum pump to evacuate, adjust the vacuum degree to 0-20Pa, heat the melting furnace, heat up and melt, keep warm and refine, and finally stop heating after completion. After solidification for 30-40 minutes, take out of the furnace to obtain a mold ingot; S3. Cut off the pouring and riser, then clean the surface of the ingot, calculate the blanking length according to the blanking weight, and cut and blank: S4. According to the size requirements of the injection mold, the ingot is forged and stretched into a rod; S5. Heat the rod material to 840-860℃ in a vacuum water quenching furnace and keep it warm for 40-80 minutes, then quickly quench and cool it to room temperature; S6, placing the rod material after quenching treatment in S5 into a freezer for cold treatment, further reducing the amount of retained austenite and promoting the transformation of martensite structure; S7, tempering the deep-cold treated rod material at 600-650°C to obtain a tempered troostite structure with excellent comprehensive properties; S8, straightening and machining the rod material processed in S7, and performing laser quenching heat treatment on the concave and convex mold surfaces after machining; S9, assembling the concave and convex molds and other components processed by S8 to obtain a high-performance injection mold.

[0015] In some embodiments, the refining temperature in step S2 is 1500-1540°C.

[0016] In some embodiments, the vacuum degree of the vacuum water quenching furnace in step S5 is not higher than 50Pa.

[0017] In some embodiments, the cold treatment temperature in step S6 ranges from -80 to -70°C.

[0018] In some embodiments, the troostite hardness in step S7 is 30-35 HRC.

[0019] In some embodiments, the thickness of the hardened layer by laser quenching heat treatment in step S8 is 0.15-0.30 mm, and the hardness is 58-62 HRC.

[0020] Beneficial effects: The beneficial effects of the present invention are as follows: (1) When mixing the ingredients, alloy elements such as Ni, Mo, and V are added to the medium carbon steel to refine the grains, improve the hardenability, and at the same time improve the strength, wear resistance, and plasticity of the material. Ni and Cr alloy elements are also beneficial to improving the corrosion resistance of the injection mold; (2) The mold material adopts vacuum induction sintering, the molten metal is non-oxidized, and the smelted metal is of high purity, which effectively improves the metallurgical quality of the material and thus improves the comprehensive performance of the material; (3) Use vacuum quenching furnace for quenching, so that the mold material is heated evenly to prevent oxidation and decarburization of the material, so as to ensure the carbon content in the martensite of the mold steel after quenching and ensure higher hardness; (4) The mold steel is cryogenically treated in a freezer to further transform the retained austenite into martensite, stabilize the structure, and thus ensure dimensional stability. This process is easier to implement than the previous nitrogen cryogenic treatment and has a lower cost. (5) The surfaces of the concave and convex molds of the injection mold are laser quenched. This process ensures that the core of the mold has good strength and toughness while also improving the hardness of the working surface, thereby increasing the service life of the mold. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0022] A high-performance injection mold material, comprising the following components in percentage by mass: C: 0.30%; Si: 0.20%; Mn: 1.2%; Cr: 1.5%; Mo: 1.5%; Ni: 0.8%; V: 0.2%, the balance is Fe.

[0023] Among them, the Si is added in the form of ferrosilicon containing 73% Si, the Mn is added in the form of ferromanganese containing 65% Mn, the Cr is added in the form of low-carbon ferrochrome containing 57% Cr, the Mo is added in the form of molybdenum plate containing 55% Mo, the Ni is added in the form of pure nickel plate, and the V is added in the form of ferrovanadium containing 50% V.

[0024] Among them, C makes the material have better comprehensive mechanical properties (strength and toughness) after heat treatment; Si has a solid solution strengthening effect and improves hardenability; Mn can prevent hot brittleness and strongly improve the hardenability of steel to improve wear resistance; Cr can increase the high-temperature oxidation resistance and corrosion resistance of oxidizing media of steel; Mo improves hardenability, reduces or inhibits the tempering brittleness of other alloying elements, and improves thermal strength; Ni has the effect of refining grains, improving the plasticity and toughness of steel, and can improve the corrosion resistance of steel; V can improve the tempering resistance of steel, has a strong secondary hardening effect, and has the effect of oxidizing grains.

[0025] The method for preparing the above-mentioned high-performance injection mold material comprises the following steps: S1. According to the mass ratio of each element, select suitable raw materials for calculation and batching; S2, put the prepared raw materials into the crucible of the vacuum induction melting furnace, cover the furnace cover, close the vent valve, start the vacuum pump to evacuate, adjust the vacuum degree to 5Pa, heat the melting furnace, melt at a high temperature, and refine at a temperature of 1500°C; finally, stop heating after completion, and take out the mold ingot after solidification for 30 minutes; S3. Cut off the pouring and riser, then clean the surface of the ingot, calculate the blanking length according to the blanking weight, and cut and blank: S4. According to the size requirements of the injection mold, the ingot is forged and stretched into a rod; S5, heating the rod material to 840°C in a vacuum water quenching furnace and keeping the temperature for 40 minutes, wherein the vacuum degree of the vacuum water quenching furnace is not higher than 50Pa, and then rapidly quenching and cooling to room temperature by water; S6, placing the rod material after quenching treatment in S5 into a freezer for cold treatment at a temperature range of -80°C, further reducing the amount of retained austenite and promoting the transformation of martensite structure; S7, tempering the deep-cold treated rod material at 600-650°C to obtain a tempered troostite structure with excellent comprehensive performance, and the troostite hardness is 30-35HRC; S8, the rod material treated in S7 is straightened and machined, and the surface of the concave and convex molds after machining is subjected to laser quenching heat treatment, and the thickness of the hardened layer of the laser quenching heat treatment is 0.15mm and the hardness is 58-62HRC; S9, assembling the concave and convex molds and other components processed by S8 to obtain a high-performance injection mold. Example

[0026] A high-performance injection mold material, comprising the following components in percentage by mass: C: 0.32%; Si: 0.22%; Mn: 1.3%; Cr: 1.6%; Mo: 1.6%; Ni: 0.9%; V: 0.25%, the balance is Fe.

[0027] Among them, the Si is added in the form of ferrosilicon containing 73% Si, the Mn is added in the form of ferromanganese containing 65% Mn, the Cr is added in the form of low-carbon ferrochrome containing 57% Cr, the Mo is added in the form of molybdenum plate containing 55% Mo, the Ni is added in the form of pure nickel plate, and the V is added in the form of ferrovanadium containing 50% V.

[0028] Among them, C makes the material have better comprehensive mechanical properties (strength and toughness) after heat treatment; Si has a solid solution strengthening effect and improves hardenability; Mn can prevent hot brittleness and strongly improve the hardenability of steel to improve wear resistance; Cr can increase the high-temperature oxidation resistance and corrosion resistance of oxidizing media of steel; Mo improves hardenability, reduces or inhibits the tempering brittleness of other alloying elements, and improves thermal strength; Ni has the effect of refining grains, improving the plasticity and toughness of steel, and can improve the corrosion resistance of steel; V can improve the tempering resistance of steel, has a strong secondary hardening effect, and has the effect of oxidizing grains.

[0029] The method for preparing the above-mentioned high-performance injection mold material comprises the following steps: S1. According to the mass ratio of each element, select suitable raw materials for calculation and batching; S2. Put the prepared raw materials into the crucible of the vacuum induction melting furnace, cover the furnace cover, close the vent valve, start the vacuum pump to evacuate, adjust the vacuum degree to 10Pa, heat the melting furnace, melt at high temperature, and refine at a temperature of 1510°C; finally, stop heating after completion, and take out the mold ingot after solidification for 35 minutes; S3. Cut off the pouring and riser, then clean the surface of the ingot, calculate the blanking length according to the blanking weight, and cut and blank: S4. According to the size requirements of the injection mold, the ingot is forged and stretched into a rod; S5, heating the rod material to 845°C in a vacuum water quenching furnace and keeping the temperature for 45 minutes, wherein the vacuum degree of the vacuum water quenching furnace is not higher than 50Pa, and then rapidly quenching and cooling the rod material to room temperature by water; S6, placing the rod material after quenching treatment in S5 into a freezer for cold treatment at a temperature range of -75°C, further reducing the amount of retained austenite and promoting the transformation of martensite structure; S7. Temper the deep-cold treated rod at 610°C to obtain a tempered troostite structure with excellent comprehensive performance, and the troostite hardness is 30~35HRC; S8, the rod material treated in S7 is straightened and machined, and the surface of the concave and convex molds after machining is subjected to laser quenching heat treatment, and the thickness of the hardened layer of the laser quenching heat treatment is 0.20mm and the hardness is 58-62HRC; S9, assembling the concave and convex molds and other components processed by S8 to obtain a high-performance injection mold. Example

[0030] A high-performance injection mold material, comprising the following components in percentage by mass: C: 0.30%, Si: 0.40%, Mn: 1.5%, Cr: 1.8%, Mo: 1.5%, Ni: 1.0%, V: 0.2%, and the balance is Fe.

[0031] Among them, the Si is added in the form of ferrosilicon containing 73% Si, the Mn is added in the form of ferromanganese containing 65% Mn, the Cr is added in the form of low-carbon ferrochrome containing 57% Cr, the Mo is added in the form of molybdenum plate containing 55% Mo, the Ni is added in the form of pure nickel plate, and the V is added in the form of ferrovanadium containing 50% V.

[0032] Among them, C makes the material have better comprehensive mechanical properties (strength and toughness) after heat treatment; Si has a solid solution strengthening effect and improves hardenability; Mn can prevent hot brittleness and strongly improve the hardenability of steel to improve wear resistance; Cr can increase the high-temperature oxidation resistance and corrosion resistance of oxidizing media of steel; Mo improves hardenability, reduces or inhibits the tempering brittleness of other alloying elements, and improves thermal strength; Ni has the effect of refining grains, improving the plasticity and toughness of steel, and can improve the corrosion resistance of steel; V can improve the tempering resistance of steel, has a strong secondary hardening effect, and has the effect of oxidizing grains.

[0033] The method for preparing the above-mentioned high-performance injection mold material comprises the following steps: S1. According to the mass ratio of each element, select suitable raw materials for calculation and batching; S2, put the prepared raw materials into the crucible of the vacuum induction melting furnace, cover the furnace cover, close the vent valve, start the vacuum pump to evacuate, adjust the vacuum degree to 15Pa, heat the melting furnace, melt at a high temperature, and refine at a temperature of 1520°C; finally, stop heating after completion, and take out the mold ingot after solidification for 35 minutes; S3. Cut off the pouring and riser, then clean the surface of the ingot, calculate the blanking length according to the blanking weight, and cut and blank: S4. According to the size requirements of the injection mold, the ingot is forged and stretched into a rod; S5, heating the rod material to 850°C in a vacuum water quenching furnace for 50 minutes, wherein the vacuum degree of the vacuum water quenching furnace is not higher than 50Pa, and then rapidly quenching and cooling to room temperature by water; S6, placing the rod material after quenching treatment in S5 into a freezer for cold treatment at a temperature range of -75°C, further reducing the amount of retained austenite and promoting the transformation of martensite structure; S7. Temper the deep-cold treated rod at 620°C to obtain a tempered troostite structure with excellent comprehensive performance, and the troostite hardness is 30~35HRC; S8, the rod material treated in S7 is straightened and machined, and the surface of the concave and convex molds after machining is subjected to laser quenching heat treatment, and the thickness of the hardened layer of the laser quenching heat treatment is 0.20mm and the hardness is 58-62HRC; S9, assembling the concave and convex molds and other components processed by S8 to obtain a high-performance injection mold. Example

[0034] A high-performance injection mold material, comprising the following components in percentage by mass: C: 0.38%; Si: 0.32%; Mn: 1.4%; Cr: 1.8%; Mo: 1.8%; Ni: 1.0%; V: 0.3%, the balance is Fe.

[0035] Among them, the Si is added in the form of ferrosilicon containing 73% Si, the Mn is added in the form of ferromanganese containing 65% Mn, the Cr is added in the form of low-carbon ferrochrome containing 57% Cr, the Mo is added in the form of molybdenum plate containing 55% Mo, the Ni is added in the form of pure nickel plate, and the V is added in the form of ferrovanadium containing 50% V.

[0036] Among them, C makes the material have better comprehensive mechanical properties (strength and toughness) after heat treatment; Si has a solid solution strengthening effect and improves hardenability; Mn can prevent hot brittleness and strongly improve the hardenability of steel to improve wear resistance; Cr can increase the high-temperature oxidation resistance and corrosion resistance of oxidizing media of steel; Mo improves hardenability, reduces or inhibits the tempering brittleness of other alloying elements, and improves thermal strength; Ni has the effect of refining grains, improving the plasticity and toughness of steel, and can improve the corrosion resistance of steel; V can improve the tempering resistance of steel, has a strong secondary hardening effect, and has the effect of oxidizing grains.

[0037] The method for preparing the above-mentioned high-performance injection mold material comprises the following steps: S1. According to the mass ratio of each element, select suitable raw materials for calculation and batching; S2, put the prepared raw materials into the crucible of the vacuum induction melting furnace, cover the furnace cover, close the vent valve, start the vacuum pump to evacuate, adjust the vacuum degree to 18Pa, heat the melting furnace, melt at a high temperature, and refine at a temperature of 1530°C; finally, stop heating after completion, and take out the mold ingot after solidification for 30 minutes; S3. Cut off the pouring and riser, then clean the surface of the ingot, calculate the blanking length according to the blanking weight, and cut and blank: S4. According to the size requirements of the injection mold, the ingot is forged and stretched into a rod; S5, heating the rod material to 850°C in a vacuum water quenching furnace for 60 minutes, wherein the vacuum degree of the vacuum water quenching furnace is not higher than 50Pa, and then rapidly quenching and cooling to room temperature by water; S6, placing the rod material after quenching treatment in S5 into a freezer for cold treatment at a temperature range of -75°C, further reducing the amount of retained austenite and promoting the transformation of martensite structure; S7. Temper the deep-cold treated rod at 640°C to obtain a tempered troostite structure with excellent comprehensive performance, and the troostite hardness is 30~35HRC; S8, the rod material treated in S7 is straightened and machined, and the surfaces of the concave and convex molds after machining are subjected to laser quenching heat treatment, and the thickness of the hardened layer of the laser quenching heat treatment is 0.25mm and the hardness is 58-62HRC; S9, assembling the concave and convex molds and other components processed by S8 to obtain a high-performance injection mold. Example

[0038] A high-performance injection mold material, comprising the following components in percentage by mass: C: 0.40%; Si: 0.40%; Mn: 1.5%; Cr: 2.0%; Mo: 2.0%; Ni: 1.2%; V: 0.4%, the balance is Fe.

[0039] Among them, the Si is added in the form of ferrosilicon containing 73% Si, the Mn is added in the form of ferromanganese containing 65% Mn, the Cr is added in the form of low-carbon ferrochrome containing 57% Cr, the Mo is added in the form of molybdenum plate containing 55% Mo, the Ni is added in the form of pure nickel plate, and the V is added in the form of ferrovanadium containing 50% V.

[0040] Among them, C makes the material have better comprehensive mechanical properties (strength and toughness) after heat treatment; Si has a solid solution strengthening effect and improves hardenability; Mn can prevent hot brittleness and strongly improve the hardenability of steel to improve wear resistance; Cr can increase the high-temperature oxidation resistance and corrosion resistance of oxidizing media of steel; Mo improves hardenability, reduces or inhibits the tempering brittleness of other alloying elements, and improves thermal strength; Ni has the effect of refining grains, improving the plasticity and toughness of steel, and can improve the corrosion resistance of steel; V can improve the tempering resistance of steel, has a strong secondary hardening effect, and has the effect of oxidizing grains.

[0041] The method for preparing the above-mentioned high-performance injection mold material comprises the following steps: S1. According to the mass ratio of each element, select suitable raw materials for calculation and batching; S2. Put the prepared raw materials into the crucible of the vacuum induction melting furnace, cover the furnace, close the vent valve, start the vacuum pump to evacuate, adjust the vacuum degree to 20Pa, heat the melting furnace, melt at high temperature, and refine at a temperature of 1540°C; finally, stop heating after completion, and take out the mold ingot after solidification for 40 minutes; S3. Cut off the pouring and riser, then clean the surface of the ingot, calculate the blanking length according to the blanking weight, and cut and blank: S4. According to the size requirements of the injection mold, the ingot is forged and stretched into a rod; S5, heating the rod material to 860°C in a vacuum water quenching furnace for 80 minutes, wherein the vacuum degree of the vacuum water quenching furnace is not higher than 50Pa, and then rapidly quenching and cooling to room temperature by water; S6. Put the rod material after S5 quenching into a freezer for cold treatment at a temperature range of -80 to -70°C to further reduce the amount of retained austenite and promote the transformation of martensite structure; S7. Temper the deep-cold treated rod at 650°C to obtain a tempered troostite structure with excellent comprehensive performance, and the troostite hardness is 30~35HRC; S8, the rod material treated in S7 is straightened and machined, and the surfaces of the concave and convex molds after machining are subjected to laser quenching heat treatment, and the thickness of the hardened layer of the laser quenching heat treatment is 0.30mm and the hardness is 58-62HRC; S9, assembling the concave and convex molds and other components processed by S8 to obtain a high-performance injection mold.

[0042] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A high-performance injection mold material, characterized in that: Includes the following mass percentage components: C: 0.30~0.40%; Si: 0.20~0.40%; Mn: 1.2~1.5%; Cr: 1.5~2.0%; Mo: 1.5~2.0%; Ni: 0.8~1.2%; V: 0.2~0.4%, the balance is Fe.

2. A high performance injection mold material according to claim 1, characterized in that: The Si is added in the form of ferrosilicon containing 73% Si, the Mn is added in the form of ferromanganese containing 65% Mn, the Cr is added in the form of low-carbon ferrochrome containing 57% Cr, the Mo is added in the form of molybdenum plate containing 55% Mo, the Ni is added in the form of pure nickel plate, and the V is added in the form of ferrovanadium containing 50% V.

3. A method for preparing a high-performance injection mold material according to claim 1 or 2, characterized in that: The steps include: S1. According to the mass ratio of each element, select suitable raw materials for calculation and batching; S2. Put the prepared raw materials into the crucible of the vacuum induction melting furnace, cover the furnace cover, close the vent valve, start the vacuum pump to evacuate, adjust the vacuum degree to 0-20Pa, heat the melting furnace, heat up and melt, keep warm and refine, and finally stop heating after completion. After solidification for 30-40 minutes, take out of the furnace to obtain a mold ingot; S3. Cut off the pouring and riser, then clean the surface of the ingot, calculate the blanking length according to the blanking weight, and cut and blank: S4. According to the size requirements of the injection mold, the ingot is forged and stretched into a rod; S5. Heat the rod material to 840-860℃ in a vacuum water quenching furnace and keep it warm for 40-80 minutes, then quickly quench and cool it to room temperature; S6, placing the rod material after quenching treatment in S5 into a freezer for cold treatment, further reducing the amount of retained austenite and promoting the transformation of martensite structure; S7, tempering the deep-cold treated rod material at 600-650°C to obtain a tempered troostite structure with excellent comprehensive properties; S8, straightening and machining the rod material processed in S7, and performing laser quenching heat treatment on the concave and convex mold surfaces after machining; S9, assembling the concave and convex molds and other components processed by S8 to obtain a high-performance injection mold.

4. The method for preparing a high-performance injection mold material according to claim 3, characterized in that: The refining temperature in step S2 is 1500-1540°C.

5. The method for preparing a high-performance injection mold material according to claim 3, characterized in that: The vacuum degree of the vacuum water quenching furnace in step S5 is not higher than 50Pa.

6. The method for preparing a high-performance injection mold material according to claim 3, characterized in that: The cold treatment temperature range in step S6 is -80 to -70°C.

7. The method for preparing a high-performance injection mold material according to claim 3, characterized in that: The troostite hardness in step S7 is 30-35 HRC.

8. The method for preparing a high-performance injection mold material according to claim 3, characterized in that: In step S8, the thickness of the hardened layer by laser quenching heat treatment is 0.15-0.30 mm, and the hardness is 58-62 HRC.